Characterization method for ash morphology of carbon fiber
Through the method of knot-making and box-type atmosphere furnace ash firing, the problem of difficult characterization of carbon fiber ash morphology is solved, and high retention and effective characterization of carbon fiber ash morphology is achieved, reducing costs and improving efficiency.
Patent Information
- Application Number
- CN202411726862.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The prior art is difficult to effectively characterize the ash morphology in carbon fibers, affecting the determination of mechanical properties, and the traditional ash firing method is costly and inefficient.
The knot sample preparation method is adopted, and the ash is fired through a box-type atmosphere furnace. The specific steps include weighing carbon fibers, knots, heating to a constant temperature of 900±20°C for 12-13 hours, and after cooling, the ash is removed for gold spraying and electron microscopy observation.
Effectively ensure the morphological integrity of carbon fiber ash, facilitate observation and determination of the morphology of silicon-based oil agents in carbon fiber, save costs, facilitate transformation, and facilitate improving the characterization efficiency of carbon fiber ash morphology.
Smart Images

Figure CN119619184A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of material characterization, and in particular relates to a method for characterizing the ash morphology of carbon fiber. Background Art
[0002] Carbon fiber is widely used in military research, industrial and civilian fields for its low weight, low creep, corrosion resistance and good mechanical properties. It is a high-performance emerging carbon material. Oil agent, as an important auxiliary agent for PAN fiber and carbon fiber, provides protection for PAN steam drawing and is eliminated during the pre-oxidation process. However, some residues (ash) will still remain in the carbon fiber after carbonization, forming a potential factor affecting the mechanical properties of carbon fiber.
[0003] The ash morphology of carbon fiber can characterize the form in which the oil remains in the carbon fiber. There are currently two views. One is that the silicon in the oil reacts with the carbon fiber to form a compound. The other view is that the small molecules in the oil enter the fiber through the pores of the PAN fiber, avoid pre-oxidation, low temperature, and high temperature cracking, and remain in the fiber. Therefore, it is necessary to design a sample preparation and characterization method that highly retains the ash morphology of carbon fiber. Summary of the invention
[0004] The purpose of the present application is to overcome the above-mentioned deficiencies in the prior art and to provide a method for characterizing the morphology of carbon fiber ash, which can effectively ensure the morphology of carbon fiber ash, facilitate the observation of the morphology of carbon fiber ash, and can preliminarily determine the morphology of silicon-based oil agent in carbon fiber and determine the presence of oil agent in the fiber; and the method is cost-saving, convenient and cheap to modify, effectively ensures the integrity of carbon fiber ash, and effectively improves the characterization efficiency of carbon fiber ash morphology.
[0005] According to a first aspect of the present application, a method for characterizing the ash morphology of carbon fiber is provided, comprising the following steps:
[0006] S1: weigh a predetermined mass of carbon fiber and tie it into a knot;
[0007] S2: placing the knotted carbon fiber in a vessel;
[0008] S3: Use a box-type atmosphere furnace, heat according to the preset temperature and time, and burn the ash under the condition of air flow;
[0009] S4: stop heating, cool, take out the vessel; push away the ash, make it stick to the conductive glue on the electron microscope sample stage, and perform gold spraying; then adjust the magnification of the electron microscope for observation.
[0010] Wherein, the predetermined mass in step S1 is 8-10 g, preferably 8 g.
[0011] Wherein, in step S1, the knotting method is self-tying.
[0012] Among them, in step S3, the heating according to the preset temperature and time is specifically: heating from below 300°C to 900±20°C with the furnace, and maintaining the constant temperature for 12-13h; preferably, heating from below 300°C to 900±10°C with the furnace, and maintaining the constant temperature for 12-13h.
[0013] Wherein, the carbon fiber is T700, T1000, M40X and M55J carbon fiber samples.
[0014] Among them, the carbon fiber is 1-3 bundles.
[0015] Wherein, the vessel is a ceramic vessel.
[0016] The traditional carbon fiber ash burning will affect the existence state of ash due to the air volume and temperature in the box atmosphere furnace, so the completion of ash cannot be guaranteed, and the morphology of carbon fiber ash cannot be fully characterized. This application innovatively prepares the carbon fiber sample by knotting, so that the sample can maintain a stable shape after ash burning, avoiding the ash presenting irregular shape or chaotic cross arrangement, making it difficult to determine the morphology of silicon-based oil in carbon fiber, and the existence of oil in fiber, which cannot be characterized.
[0017] Furthermore, during the ash firing process, if the temperature rises too fast, the ash will easily present an irregular shape or a chaotic cross arrangement, while if the temperature rises too slowly, the characterization efficiency will be reduced. Therefore, for the ash firing process, a box-type atmosphere furnace is used for heating (the circular hole of the furnace door is opened during burning, and natural ventilation and oxidation are performed), and the ash is fired under the condition of air being introduced. The specific firing temperature is 900±20℃, which can ensure the integrity of the sample ash, and the firing time is 12-13h. Preferably, the firing temperature is 900±10℃.
[0018] Compared with the prior art, the present application has the following beneficial effects: the characterization method of carbon fiber ash morphology provided by the present application is to knot the carbon fiber so that the tow itself forms a relatively stable sample for firing; at the same time, the temperature and time of the ash firing process are studied accordingly according to the special sample morphology, so that the characterization method can effectively ensure the morphology of the carbon fiber ash, facilitate the observation of the morphology of the carbon fiber ash, and preliminarily determine the morphology of the silicon-based oil in the carbon fiber and determine the presence of the oil in the fiber. In addition, the method saves costs, is convenient and cheap to modify, effectively guarantees the integrity of the carbon fiber ash, and effectively improves the characterization efficiency of the carbon fiber ash morphology. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solution of the present disclosure, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 This is a diagram of a knotting method according to an embodiment of the characterization method of the present application.
[0021] Figure 2 It is a comparison chart of the ash morphology according to the characterization method embodiment of the present application and the morphology of the ash after firing in the traditional sample preparation method.
[0022] Figure 3 The ash SEM images of samples with oil contents of 0.6% and 0.8% according to the characterization method Example 1 of the present application.
[0023] Figure 4 The ash SEM images of samples with oil contents of 0.6% and 0.8% according to the characterization method Example 2 of the present application.
[0024] Figure 5 The ash SEM images of samples with oil contents of 0.6% and 0.8% according to the characterization method Example 3 of the present application.
[0025] Figure 6 The ash SEM images of samples with oil contents of 0.6% and 0.8% according to the characterization method Example 4 of the present application.
[0026] Figure 7 The ash SEM images of samples with oil contents of 0.6% and 0.8% according to the characterization method Example 5 of the present application.
[0027] Figure 8 This is a diagram of the traditional sample preparation method.
[0028] Fig. 9 This is the ash SEM image of the carbon fiber product prepared by traditional sampling method. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the specific embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other in the absence of conflict. The present application will be described in detail below in conjunction with the embodiments.
[0030] The method for characterizing the ash morphology of carbon fiber of the present application comprises the following steps:
[0031] S1: Weigh 8-10g of carbon fiber and tie a knot;
[0032] S2: placing the knotted carbon fiber in a vessel;
[0033] S3: Use a box-type atmosphere furnace, raise the temperature from below 300℃ to 900±20℃, maintain the constant temperature for 12-13h, and burn the ash under the condition of air;
[0034] S4: stop heating, cool, take out the vessel; push away the ash, make it stick to the conductive glue on the electron microscope sample stage, and perform gold spraying; then adjust the magnification of the electron microscope for observation.
[0035] The predetermined mass in step S1 is 8-10 g, preferably 8 g. The knotting method is self-knotting (such as Figure 1 shown).
[0036] In step S3, heating according to the preset temperature and time is specifically: heating from below 300°C to 900±20°C with the furnace, and maintaining the constant temperature for 12-13h; preferably, heating from below 300°C to 900±10°C with the furnace, and maintaining the constant temperature for 12-13h.
[0037] The carbon fibers are T700, T1000, M40X and M55J carbon fiber samples.
[0038] Specific examples for different carbon fiber samples are shown below.
[0039] Example
[0040] Examples 1-5 respectively select carbon fiber product samples 1-sample 5 with different mechanical properties for sample preparation and characterization; among them, sample 1 is a T700 carbon fiber product, sample 3 is a T1000-6K carbon fiber product, sample 3 is a T1000-12K carbon fiber product, sample 4 is an M40X carbon fiber product, and sample 5 is an M55J carbon fiber product.
[0041] The method for characterizing the ash morphology of the carbon fiber of Examples 1-5 comprises the following steps:
[0042] S1: Weigh 8g of carbon fiber and tie a knot;
[0043] S2: placing the knotted carbon fiber in a ceramic dish;
[0044] S3: Using a box-type atmosphere furnace, the temperature is raised from below 300°C to 900±10°C, and the constant temperature is maintained for 12-13h (the specific firing parameters of each embodiment are shown in Table 1), and the ash is fired under the state of air (open the round hole of the furnace door during burning, and oxidize by natural ventilation);
[0045] S4: stop heating, cool, take out the vessel; push away the ash, make it stick to the conductive glue on the electron microscope sample stage, and perform gold spraying; then adjust the magnification of the electron microscope for observation.
[0046] The product parameters and ash burning process parameters of each example sample are specifically shown in Table 1.
[0047] Table 1 Product parameters and ash content of each example sample
[0048]
[0049]
[0050] Optimal firing process parameters were developed for different samples; for example, for Examples 4 and 5, both of which were high modulus samples, the firing temperature was slightly lowered to 900°C and fired for 12 hours, which could better maintain the ash morphology of the samples. Figure 3-Figure 7 As shown. It can be seen from the attached figure that the ash morphology of the carbon fiber sample obtained by the characterization method of the present application is clear, complete and easy to observe. For example, the ash of Examples 1 and 3 is fibrous, the ash of Example 2 is more severely crossed, but can maintain a relatively uniform thickness; Example 3 is root-like, with large differences in thickness and extremely severe bifurcation. The different ash sample morphologies indicate that the arrangement of the oil in the fiber is different, which has a certain effect on the mechanical properties of the product. In addition, the sample ash morphology of Example 1 ( Figure 3 ), after comparison, it was found that the sample ash was fibrous, and the fiber diameter changed due to different oil content, indicating that different amounts of oil had different abilities to penetrate into the fiber. The smaller the diameter of the fibrous ash, the more small particles of oil, and the deeper it penetrated into the fiber.
[0051] In order to further illustrate the beneficial effects of the characterization method of the present application, the existing traditional characterization methods are listed for comparison. The ash morphology after firing by the traditional carbon fiber sample preparation method and the sample preparation method of the present application is shown in the figure. Figure 2As shown in the figure, it can be seen that the sample preparation method selected by the characterization method of the present application has a more regular and complete ash morphology after firing. The traditional carbon fiber sample preparation method and ash SEM appearance are shown in the figure. Figure 8 and Fig. 9 As shown. Among them, under the traditional carbon fiber sample preparation method, the ash sintering process has a sintering temperature of 900°C and a time of 11 hours. Fig. 9 It can be seen that the traditional sample preparation method and ash burning characterization method, the carbon fiber ash morphology is severely cross-arranged and uneven in size, which cannot well guarantee the integrity and morphology of the carbon fiber ash, and is not conducive to observing the morphology of the carbon fiber ash.
[0052] In summary, the characterization method of the present application can effectively ensure the morphology of carbon fiber ash, facilitate the observation of the morphology of carbon fiber ash, and can preliminarily determine the morphology of silicon-based oil in carbon fiber and determine the presence of oil in the fiber. In addition, the method saves costs, is convenient and cheap to modify, effectively ensures the integrity of carbon fiber ash, and effectively improves the characterization efficiency of carbon fiber ash morphology.
[0053] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present disclosure.
[0054] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for characterizing carbon fiber ash morphology, characterized in that: The following steps are involved: S1: weigh a predetermined mass of carbon fiber and tie it into a knot; S2: placing the knotted carbon fiber in a vessel; S3: Use a box-type atmosphere furnace, heat according to the preset temperature and time, and burn the ash under the condition of air flow; S4: stop heating, cool, take out the vessel; push away the ash, make it stick to the conductive glue on the electron microscope sample stage, and perform gold spraying; then adjust the magnification of the electron microscope for observation.
2. The method for characterizing carbon fiber ash morphology according to claim 1, characterized in that: The predetermined mass in step S1 is 8-10 g.
3. The method for characterizing the ash morphology of carbon fiber according to claim 1, characterized in that: In step S1, the knotting method is self-tying.
4. The method for characterizing the ash morphology of carbon fiber according to claim 1, characterized in that: In step S3, the heating according to the preset temperature and time is specifically: heating from below 300°C to 900±20°C with the furnace, and maintaining the constant temperature for 12-13h.
5. The method for characterizing carbon fiber ash morphology according to claim 4, characterized in that: The heating according to the preset temperature and time specifically includes: heating from below 300° C. to 900±10° C. with the furnace, and maintaining the constant temperature for 12-13 hours.
6. The method for characterizing carbon fiber ash morphology according to claim 1, characterized in that: The carbon fibers are T700, T1000, M40X and M55J carbon fiber samples.
7. The method for characterizing carbon fiber ash morphology according to claim 1, characterized in that: The carbon fibers are in 1 to 3 bundles.
8. The method for characterizing carbon fiber ash morphology according to claim 1, characterized in that: The vessel is a ceramic vessel.
Citation Information
Patent Citations
Method for joining polyacrylonitrile-based carbon fiber precursors
CN115303892A
Pretreatment method for carbon fiber sample test
CN116990109A
SiBCN interface layer, SiCf / SiC ceramic-based composite material protected by SiBCN interface layer and preparation method of SiCf / SiC ceramic-based composite material
CN117945764A
Polyacrylonitrile-based carbon fiber and preparation method thereof
CN118880495A
Crucible for testing ash content of carbon fiber
CN215541010U